2020
DOI: 10.1108/jiabr-09-2018-0143
|View full text |Cite
|
Sign up to set email alerts
|

Unified theory of firm: an empirical analysis

Abstract: Purpose Four main strategies required for firms to be able to achieve their main objectives in organizations under the unified theory of the firm are technological advance, intellectual development, spirituality conducts and customer satisfaction concern. This study aims to explore the inclination of firms to adopt all these strategies in, factors that contribute to the adoption of all these strategies and significant relationship between these strategies of firms in the context of Malaysian firms. Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although the UTAUT has been applied in most information systems, other studies have used the theory for research that is being carried out in other fields. For example, in their study, Duasa, Sarif, and Sabian (2019) used the UTAUT in relation to Malaysian firms. They found that the strategies of the unified theory of the firm significantly contributed to the education level of managers.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Although the UTAUT has been applied in most information systems, other studies have used the theory for research that is being carried out in other fields. For example, in their study, Duasa, Sarif, and Sabian (2019) used the UTAUT in relation to Malaysian firms. They found that the strategies of the unified theory of the firm significantly contributed to the education level of managers.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…It is supraising that the number of sharia shares listed on the exchange continues to experience a significant increase, especially with the 2015-2019 PMS Roadshow programme, as shown in the following figure. The significant development of Islamic stocks is an indicator that Muslim and non-Muslim investors are starting to glance at Islamic-based stocks (Al Amine, 2016;Sherif, 2016;Ahmed, 2019;Al Balooshi, 2020;Duasa, et. al., 2020).…”
Section: Introductionmentioning
confidence: 99%